Epidemiology, Clinical Conditions, Pathogenesis and Mechanism of Resistant of Acinetobacter baumannii: A Narrative Review - Uddin, Bhuiyan Mohammad Mahtab; Rahman, Md Anisur; Yeasmin, Mst Marufa; Mahjabin, Mosfika; Chowdhury, Sarowar Jahan; Ahmed, Iftikhar (Bangladesh Journal of Medical Microbiology, 2023)
The world is facing a growing threat from multidrug-resistant (MDR) gram negative “superbugs,” such as Acinetobacter baumannii. This morbidity and mortality loss caused there of indirectly hampers the economic developments in countries. These multidrug-resistant A. baumannii worldwide represents a major public health problem. The development of antibiotics decreased the mortality among the human and animals leading to a better life expectancy. But the injudicious use of antimicrobials and selection pressure the microbes have developed resistance which became more prominent during last few decades. High antimicrobial resistance was observed against all β-lactam and non- β-lactam antibiotics by the MBL producers. In developing countries also, the misuse and underuse of antimicrobials due to lack of awareness of patients, medical workers and financial problems emerged the antimicrobial resistant strains. Due to rapid globalization of human population by travel and other factor these resistant strains spread easily between developed and developing countries making it a global problem. Bangladesh Journal of Medical Microbiology, July 2023;17 (2):88-92